Hantavirus infection in patients with fever of unknown origin and in small mammals in the Baikal region - N. A. Bolotova; M. A. Khasnatinov; A. V. Lyapunov; E. L. Manzarova; I. S. Solovarov; L. N. Yashina; R. .. Yanagihara; G. A. Danchinova (Acta Biomedica Scientifica, 2017)
Background. Hantavirus infections are one of the most important zoonotic diseases in the Russian Federation. However, the pathogenicity of Hantaviruses circulating in Siberia is still unknown. The aim of the study was to assess the incidence of Hantavirus infection in patients with fever of unknown origin from Irkutsk region and adjacent territories. Materials and methods. Serum samples collected in 2016 from individuals with symptoms of health deterioration were screened by ELISA to investigate possible Hantavirus infection, in addition to tick-borne infections. Depending on date of tick bite specific immunoglobulin G (IgG) and immunoglobulin M (IgM) antibodies to tick-borne encephalitis, borreliosis and Hantavirus were tested by ELISA or screened by PCR for tick-borne encephalitis, borreliosis, human granulocytic anaplasmosis and monocytic erlychiosis RNA/DNA. Results. Out of 92 serum samples, 6.5 % were positive for hantavirus-specific antibodies, which is at least twice higher than the seroprevalence among healthy people in the Irkutsk region. IgM and IgM+IgG antibodies were found in 5.4 % of cases, while IgG antibodies - in 1.1 % of cases. The clinical symptoms among sero-positive patients were fever, skin lesion, fatigue syndrome, headache and lymphadenitis. IgM antibodies to borreliosis were found in two hantavirus sero-positive cases. Lung tissues from small mammals captured in 2016 were screened by ELISA for the presence of Hantavirus antigen. Hantaviral antigen was detected in 6.3 % of 48 samples. Conclusions. Thus, present and previous studies demonstrate existence of natural foci of Hantavirus infections in addition to tick-born infections in the territory of the Irkutsk region.